Will environmental changes reinforce the impact of global warming on the prairie–forest border of central North America?. Issue 7 (4th September 2009) - Frelich, Lee E; Reich, Peter B
Abstract : Within the next 50–100 years, the warming climate will have major effects on boreal and northern hardwood forests situated near the prairie–forest border of central North America. This biome boundary shifted to the northeast during past episodes of global warming, and is expected to do so again. The climate of the future will likely lead to higher mortality among mature trees, because of the greater frequency of droughts, fires, forest‐leveling windstorms, and outbreaks of native and exotic insect pests and diseases. In addition, increasing populations of native deer and European earthworm invasions will inhibit the establishment of tree seedlings. The expected net impact of these factors will be a "savannification" of the forest, owing to the loss of adult trees at a rate faster than that at which they can be replaced. This will cause a greater magnitude and more rapid northeastward shift of the prairie–forest border, as compared with a shift solely attributable to the direct effects of temperature change.